Номінування різних форм психічної діяльності людини в староукраїнських пам'ятках кін. XVI–XVII ст. - Гриценко, Світлана Павлівна (Київський національний університет імені Тараса Шевченка)
Экспрессивная лексика украинского языка конца XVI–XVII веков представляет национальную ментальность, характеризирует все сферы человеческой деятельности. В письменных источниках она представлена как оригинальными единицами, так и заимствованиями, большая часть которых является полонизмами. В номинировании различных форм психической деятельности человека принимають участие лексемы, принадлежащие различным частям речи.

The expressive lexics of Ukrainian language in the end of XVI–XVII century appears to be a representant of national mentality, it characterises all aspects of human activities. It is presented in the literate sources either by native or by adopted language units and most of the adoptions have Polish roots. Lexemes, which take part in naming different forms of human phychoactivity, belong to different parts of speech.
Keywords: експресивна лексика; запозичення; питомі одиниці; понятійне поле